The Ice Breaking Method Effectiveness On Students’ Enthusiasm In Learning English At SMPN 1 Saluputti - Aris Kaban Sendana; Rachel Rachel (LPPM UKI Toraja, 2021)
The Ice Breaking Method Effectiveness on students’ Enthusiasm in Learning English at SMPN 1 Saluputti. Students at junior high school are majorly teenagers that biologically transform from children to adolescence. This phase effects the students tend to have lack of confidence. This research to verify whether the ice breaking methods is effective on students’ enthusiasm in learning English at SMPN 1 Saluputti. The objective of this research is to find the effectiveness of the ice breaking method to improve the students’ enthusiasm in learning English at SMPN 1 Saluputti. This research is a kind of descriptive quantitative method. The subject of this research was the ninth grade students at SMPN 1 SALUPUTTI. The data of this research was collected by questionnaire. Then the data was analyzed by Likert Scale. The result of the findings about the effectiveness of the ice breaking method to improve the students’ enthusiasm in learning English at SMPN 1 Saluputti.is effective. It can be seen on the the students statement in the first questionnaire result obtained 74.5% that falling into strongly agree category and the students statement in the second questionnaire result obtained 88.3% with strongly agree category. Based on the results of this research, the researcher concludes that most of students have an increased enthusiasm in learning English when the teacher use the ice breaking method in the learning proses. So, the used of ice breaking method on students enthusiasm in lerning English at SMPN 1 Saluputti is effective.